The Venous Antithrombotic Effect of LF 1351 in the Rat following Oral Administration - Millet, Jean; Theveniaux, Jocelyne; Brown, Neil L (Thrombosis and Haemostasis, 1992)
The venous antithrombotic effects of a novel chemical entity, LF 1351, were investigated in rats following single oral administration, in comparison with i.v. administered heparin. LF 1351 demonstrated a dose-related antithrombotic effect in three models of venous thrombosis. The compound was approximately equipotent in two models involving complete stasis of the vena cava and administration of factor Xa or porcine serum, giving respective ED50 values of 48.7 mg/kg and 36.7 mg/kg. LF 1351 was less effective in a model involving partial stasis in the presence of an endothelial lesion. In this case, the antithrombotic effect did not exceed 60-65%, the ED50 being 150 mg/kg. Heparin (50-300 μg/kg; 7.5-45.0 U/kg) was effective in all three models. At the approximate ED80 value against factor Xa-induced thrombosis (75 mg/kg) the antithrombotic effect of LF 1351 persisted for 6 h. The antithrombotic effect of LF 1351 (300 mg/kg) occurred without significant changes in APTT or thrombin time.